2016
DOI: 10.1155/2016/7126080
|View full text |Cite
|
Sign up to set email alerts
|

An Operational Matrix of Fractional Differentiation of the Second Kind of Chebyshev Polynomial for Solving Multiterm Variable Order Fractional Differential Equation

Abstract: The multiterm fractional differential equation has a wide application in engineering problems. Therefore, we propose a method to solve multiterm variable order fractional differential equation based on the second kind of Chebyshev Polynomial. The main idea of this method is that we derive a kind of operational matrix of variable order fractional derivative for the second kind of Chebyshev Polynomial. With the operational matrices, the equation is transformed into the products of several dependent matrices, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…Comparison between numerical results of four numerical methods are listed in Table for Example case II with various choices of n and l = 1. From this comparison, we obtain the introduced method in this article that is applicable and gives highly accurate results comparing with the results given in El‐Mesiry, Liu et al, and Maleknejad et al While in Table , we bring results of the maximum absolute errors of the method given in Liu et al and our suggested method for Example case II with disjoint values of l and n . From the aforementioned results in Table , the values of E max using the proposed method are smaller than that given in Liu et al with the same size of Chebyshev polynomials of the second kind.…”
Section: Illustrative Examplesmentioning
confidence: 54%
See 4 more Smart Citations
“…Comparison between numerical results of four numerical methods are listed in Table for Example case II with various choices of n and l = 1. From this comparison, we obtain the introduced method in this article that is applicable and gives highly accurate results comparing with the results given in El‐Mesiry, Liu et al, and Maleknejad et al While in Table , we bring results of the maximum absolute errors of the method given in Liu et al and our suggested method for Example case II with disjoint values of l and n . From the aforementioned results in Table , the values of E max using the proposed method are smaller than that given in Liu et al with the same size of Chebyshev polynomials of the second kind.…”
Section: Illustrative Examplesmentioning
confidence: 54%
“…Definition Variable‐order Caputo fractional derivative () The variable‐order fractional derivative definition of order α ( t ) for the function u ( t ) ∈ C m [0, b ] can be defined in the Caputo sense as follows: Dαfalse(tfalse)ufalse(tfalse)=1normalΓfalse(1αfalse(tfalse)false)0+tfalse(tτfalse)αfalse(tfalse)ufalse(τfalse)dτ+ufalse(0+false)ufalse(0false)normalΓfalse(1αfalse(tfalse)false)tαfalse(tfalse). …”
Section: Preliminaries and Notationsmentioning
confidence: 99%
See 3 more Smart Citations